Flotation separation of molybdenite from talc using a new inhibitor Artemisia sphaerocephala Krasch gum. (1st December 2021) - Li, Changbin; Zhang, Guofan; Xun, Luobing; Liu, Hongjiang; Shi, Qing
Highlights: ASKG had a good depression effect on both molybdenite and talc. SBX enhanced the floatability of molybdenite without affecting the depression of ASKG on talc. ASKG adsorpted on talc surface through hydrogen bond and hydrophobic interaction in physical adsorption. The reagents of SBX and ASKG reacting prior to molybdenite would hinder the adsorption of the latter reagent on molybdenite, thus affecting the floatability of molybdenite. Abstract: In the flotation of sulfide minerals, the separation of molybdenite and talc is a difficult problem. Talc is the main gangue mineral of molybdenite, it has good natural hydrophobicity and a similar layered structure as molybdenite, so inhibitors are often used to separate them. But the reverse flotation method is often used to inhibit molybdenite, and the separation effect is not satisfactory. Therefore, an effective inhibitor is greatly needed. Here we showed a new inhibitor ASKG to separate molybdenite from talc. In microflotation tests, it was found that ASKG has a good depression effect on both molybdenite and talc. By adding collector SBX, the floatability of molybdenite can be enhanced without affecting the depression of ASKG on talc, and the effective separation of the two can be realized. The FTIR analyses and adsorption measurements revealed that the adsorption of ASKG on the talc surface occurred through hydrogen bond and hydrophobic interaction in physical adsorption. In addition, the competitive adsorption of ASKG and SBX on the surface of molybdenite was explored, and it was found that the first reagent reacted with molybdenite will hinder the adsorption of the later reagent on molybdenite and affect the floatability of molybdenite. The results showed that ASKG plays an excellent role in the separation of molybdenite and talc by positive flotation, which is of great significance for the separation of other minerals in mineral processing.